Analisis Risiko Investasi Pasar Saham Syariah dengan Pendekatan Probabilistik pada Ketidakpastian Ekonomi - Alfi Maulana Rasyid; Elis Ratna Wulan (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study analyzes investment risk using a probabilistic approach under conditions of economic uncertainty, using a case study of Islamic investment instruments in Indonesia. Using the Value at Risk (VaR) method based on Monte Carlo simulation and GARCH volatility modeling, this study evaluates Islamic stock portfolios for the period 2022-2025. The results show that the probabilistic approach is capable of estimating the maximum potential investment loss with good accuracy at the 95% confidence level, but has limitations in capturing extreme price movements at the 99% confidence level. The main contribution of this study is the integration of Islamic risk management principles into a modern probabilistic framework, which is novel in the existing literature. This study fills a research gap regarding the application of the probabilistic approach to Islamic investment instruments in emerging markets characterized by high volatility. The research findings provide important implications for Islamic investors and regulators in managing risk exposure amidst global economic uncertainty.